Fostering meaningful learning experiences through student engagement - Ktoridou, Despo 1968-; Doukanari, Eli; Eteokleous, Nikleia 1979- (IGI Global, 2021)
"The book presents the latest scholarly information on curriculum development, instructional design, and pedagogical methods fostering student engagement learning initiatives and meant to open new doorways to future research activities regarding both face-to-face and online instructor roles"--